2004
DOI: 10.3168/jds.s0022-0302(04)73324-x
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol in Saliva and Plasma of Cattle After ACTH Administration and Milking

Abstract: Interest in the measurement of salivary cortisol has increased recently because saliva can be easily collected before and after an imposed stress. This study evaluated the relationship between plasma and salivary concentrations of cortisol following ACTH administration in calves (experiment 1) and machine milking of adult cows (experiment 2). A catheter was inserted into the jugular vein of all animals 72 h before the beginning of experiments. Blood and saliva samples were collected before and after ACTH admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 26 publications
9
87
2
7
Order By: Relevance
“…At the same time, CORT levels measured before, during and after ACTH administration were similar to those observed by other authors (Negrão et al 2004). In fact, plasma CORT concentration after ACTH administration is an appropriate characteristic to study stress response in dairy animals (Fulkerson & Jamieson 1982;Negrão et al 2010).…”
Section: Acth Administrationsupporting
confidence: 73%
See 1 more Smart Citation
“…At the same time, CORT levels measured before, during and after ACTH administration were similar to those observed by other authors (Negrão et al 2004). In fact, plasma CORT concentration after ACTH administration is an appropriate characteristic to study stress response in dairy animals (Fulkerson & Jamieson 1982;Negrão et al 2010).…”
Section: Acth Administrationsupporting
confidence: 73%
“…In those animals, heat stress has also been associated with lower food intake, increase in the negative energy balance and loss in milk production (Igono et al 1992;Chaiyabutr et al 2008;Shehab-El-Deen et al 2010). In general, cortisol (CORT) is an appropriate biological endpoint for the investigation of hypothalamic-pituitary-adrenal (HPA) axis, and exogenous administration of adrenocorticotropic hormone (ACTH) can be used to study the relationship between the HPA axis activity, cortisol release and stress in domestic animals (Negrão et al 2004(Negrão et al , 2010. In general, CORT has been associated with physiological adjustments to tolerate stressful conditions (Wise et al 1988;Ronchi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Taking saliva cortisol samples to assess stress is a noninvasive and an in itself stress-free method compared with taking blood samples, and it has been shown that cortisol levels in saliva and plasma correlate well (Cook et al, 1996;Schö nreiter and Zanella, 2000;Negrao et al, 2004). This method is popular in pigs, because they react strongly to handling and fixation, which are often necessary for taking blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the level could be lower than in blood (e.g. about 10 times less in saliva; Negrão et al, 2004); the hormone could be conjugated before excretion (e.g. urine and faeces, and, again, transformed by bacteria in the gut; furthermore, the level could also show some fluctuations (e.g.…”
Section: Cortisolmentioning
confidence: 99%
“…Broom (1988) observed a hyper-reactivity in animals under chronic stress after ACTH challenges and supports the relationship between high basal cortisol levels and chronic stress, while Weiss et al (2004) consider the hyper-reactivity under ACTH challenges to be true in pigs, but not in cattle. Undoubtedly, the interpretation of the basal blood cortisol is not easy because it is affected by a variety of factors, including the following: circadian rhythms ; sampling (Negrão et al, 2004); restraint (Bertoni et al, 2005a); stage of lactation (Bertoni et al, 2006a); coitus and nursing (Manteca, 1998); milking (Bertoni et al, 2005a;Rushen et al, 2007), degree of habituation (von Borell, 2001;Smith and Dobson, 2002) (Bertoni et al, 1991;Rushen et al, 2007).…”
Section: Cortisolmentioning
confidence: 99%